PENGARUH AIR LINDI TEMPAT PEMBUANGAN AKHIR SAMPAH SUWUNG TERHADAP KUALITAS AIR TANAH DANGKAL DI SEKITARNYA DI KELURAHAN PEDUNGAN KOTA DENPASAR - -, Arbain; Mardana, NK; Sudana, IB (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 3 No 2, 2012)
Garbage Dump (GD) of Suwung which is located at the Village of Pedungan, South Denpasar District is dump ofgarbage coming from the City of Denpasar and Badung Regency. GD of Suwung operates with open dumping so that it ispotential to pollute the surrounding shallow ground water. This study was conducted to know the characteristics ofleachate, its effect to the quality of water around the GD and the quality of water according to water standard quality forthe need of drinking water and its status of its Pollution Index.This study was conducted with the taking of water sampleof leachate, taken in two locations, in the northern part of the GD and in the southern part of the GD. The water sample ofshallow ground water was taken at 4 location samples by considering the distance of the location from the GD. In eachlocation sample, 10 sample points were taken which were then composited into one. The analysis of physical, chemical,and microbiological characteristics of leachate and the quality of shallow ground water was done in-situ and in thelaboratory. The results obtained from the analysis compared them descriptively with tables and graphs and calculation ofthe Pollution Index (PI) of the quality of shallow underground water.The results of the study show that all the parameters of leachate did not meet the requirement of Standard Qualityof Domestic Waste Water Regulation of Bali Governor Number 8 of 2007. The quality of leachate from the Suwung GDaffected the quality of shallow ground water in all locations (L1, L2, and L3). The greatest effect in the location whosedistance is between 1 – 125 m from the GD (L1) is parameter of TDS, BOD5, COD, DO, PO4, NO3, NO2, NH3, Fe, Cl,H2S, Phenol, and total Coliform, the location whose distance is between 125 – 250 m from the GD (L2) is the parameter of TDS, BOD5, COD, DO, PO4, NO2, NH3, Cl, H2S, Phenol, and total Coliform, and the location whose distance isbetween 250 – 375 m from the GD (L3) is the parameter of BOD5, COD, DO, PO4, NO2, NH3, H2S, Phenol, and TotalColiform. At the location is far from the GD as a control location (L4) is the parameter of DO, PO4, NO2, NH3, Phenol,and Total Coliform. For the Index of Pollution in the sample locations L1, L2, and L3 was categorized into heavilypolluted level and L4 (as control) was categorized into lightly polluted level.
Keywords: Garbage Dump, Leachate, Quality of Ground Water